2015
DOI: 10.1093/conphys/cov005
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and amphibians: effects on life history and susceptibility to the infectious pathogen,Batrachochytrium dendrobatidis

Abstract: Carotenoids are components of an animal’s diet that are considered beneficial because they typically provide increased immune capacity. However, little research has been done in amphibians. We found that carotenoids can cause lower survival, slower development and growth in amphibians, and no mitigating effects against a common amphibian disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 59 publications
3
24
1
Order By: Relevance
“…In a broader context, the effect of dietary carotenoids on larval survival, growth and development has been investigated in six anuran species (including P. corroboree ), and findings have been inconsistent. Significant effects of dietary carotenoids on larval survival have only been reported for two species, with carotenoids found to have a positive effect in one species ( O. pumilio ; Dugas et al, ), and a detrimental effect in another ( R. sylvatica ; Cothran et al, ). In regard to growth and development, dietary carotenoids have been found to have a significant positive effect in one anuran species ( S. tropicalis; Ogilvy & Preziosi, ), a significant negative effect in two species (H. versicolor and R. sylvatica ; Cothran et al, ), and no significant effect in another two species ( P.corroboree and A.callidryas ; Ogilvy et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a broader context, the effect of dietary carotenoids on larval survival, growth and development has been investigated in six anuran species (including P. corroboree ), and findings have been inconsistent. Significant effects of dietary carotenoids on larval survival have only been reported for two species, with carotenoids found to have a positive effect in one species ( O. pumilio ; Dugas et al, ), and a detrimental effect in another ( R. sylvatica ; Cothran et al, ). In regard to growth and development, dietary carotenoids have been found to have a significant positive effect in one anuran species ( S. tropicalis; Ogilvy & Preziosi, ), a significant negative effect in two species (H. versicolor and R. sylvatica ; Cothran et al, ), and no significant effect in another two species ( P.corroboree and A.callidryas ; Ogilvy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dugas, Yeager, and Richards‐Zawacki () reported that dietary carotenoids resulted in female strawberry poison frogs ( Oophaga pumilio ) producing more offspring, resulting from an increase in the rate at which tadpoles completed metamorphosis, and a higher number of tadpoles transitioning to metamorphosis. In contrast, Cothran et al () recently reported that dietary carotenoids reduced the rate of growth and development in wood frogs ( Rana sylvatica ) and gray tree frogs ( Hyla versicolor ), and reduced survival to metamorphosis in wood frogs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this study did not consider cutaneous microbial dynamics, so it is unclear whether ineffective pathogen resistance in these two species was a consequence of deficient microbial community dynamics, such as the complete absence of effective antiBd bacteria [ 36 ]. Interestingly, Cothran et al [ 37 ] also reported reduced growth rates and survivorship of individuals fed a carotenoid supplemented diet, indicating that the dose administered may have been detrimental to these anuran species. Of note, results from our laboratory show no significant effect of carotenoid supplementation on juvenile or postmetamorphic growth, development or survival of P. corroboree (Byrne and Silla unpublished data).…”
Section: Aq4mentioning
confidence: 91%
“…Additional research is also urgently needed to test how the differences in cutaneous bacterial communities observed as a result of dietary carotenoid supplementation influence disease resistance in endangered amphibians. A recent study by Cothran et al [ 37 ] reported no mitigating effects of dietary carotenoids against Bd infection in two common amphibian species, Lithobates sylvaticus and Hyla versicolor. However, this study did not consider cutaneous microbial dynamics, so it is unclear whether ineffective pathogen resistance in these two species was a consequence of deficient microbial community dynamics, such as the complete absence of effective antiBd bacteria [ 36 ].…”
Section: Aq4mentioning
confidence: 95%